Effect of Aerobic Exercise on Respiratory Parameters In Untrained And Trained Subjects - Dr. Jayant Kumar , Kamla Choudhary, Sunita Choudhary, (International Journal of Scientific Research and Management (IJSRM), 2015)
Physical fitness is required not only by athletes for better performance but also by non-athletes for maintenance of physical and mental health. The aim of the study was to assess the role of aerobic exercise on respiratory parameters among untrained and trained subjects. The present study was conducted in the Dept. of Physiology, Dr. S.N. Medical College, Jodhpur after ethical approval. Informed written consent was obtained from all the subjects included in the study. In this study total 200 male subjects were included, which were further divided in two groups. Group I included 100 randomly selected untrained male subjects (medical students) at the beginning of their training period. Group II: It included the same 100 healthy medical students, as in group I, but after their training period of 3months duration. Group III: 100 randomly selected male Athletes participating in city/district/state competition constituted the trained group. All the subjects in untrained group participated in aerobic exercise for three months. Untrained Subjects were assessed for pulmonary function tests (FEV1 and PEFR), with the help of computerized spirometer (Helios 401, RMS Recorders & Medicare Systems) before and after training. Values obtained were compared with data obtained from athletes. Aerobic exercise training resulted in improved ventilatory functions in untrained, in the form of increase in the forced expiratory volume at the end of 1st second (FEV1; p